STUDI LITERATUR PEMANFAATAN MEDIA CUACA SMART BERBANTUAN PENDEKATAN PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI IPAS MENGENAL CUACA DAN PENGARUHNYA TERHADAP KEHIDUPAN MANUSIA UNTUK SEKOLAH DASAR - Kurniawan Budi Susanto, Dimas; Handoyo, Eko Handoyo; Sri Sumartiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effects of using smart weather learning media assisted by problem-based learning on 3rd grade elementary school students' learning about weather and its impact on human life. The library research method, also called literature study, is by collecting data and then processing the research data. This research data was obtained from several previous studies. Data were analyzed by data reduction and presentation. The results of the analysis indicate that the science learning media is very suitable for use. The advantages of PBL-based smart weather media are that it can create classes, can use ready-to-use content, and can create content that suits the wishes or needs of its users. Thus, learning can improve student learning outcomes and become an alternative solution in implementing effective learning media in science learning.